1 - Globalisation and Social Security in Low-Income Countries: The Case of Côte d'Ivoire: 10.4314/ad.v28i2.22174 - Baye , Francis Menjo (Africa Development, 2003)
Drawing on empirical evidence from Côte d'Ivoire, this article emphasises the need to reform existing social security systems in low-income economies in order to alleviate poverty and guarantee economic security. Following a background perspective, the article presents a brief overview of existing formal and informal social security systems and examines their merits and limitations. Next, the challenges of globalisation for social security systems in a low-income country context are discussed. Here, it is argued that the impact and challenges of globalisation are real and increase the need to redesign social security. The article concludes by suggesting that social security provision in low-income countries should be organised in a complementary way, drawing on the strengths of both formal and informal arrangements. Future reforms should attempt to combine poverty alleviation with measures designed to promote economic development and international economic integration.